The Effect of Foot Reflexology Massage on the Sleep Quality of Elderly Women With Restless Leg Syndrome - Amine Abbasi Fakhravari; Farideh Bastani; Hamid Haghani (Iran University of Medical Sciences, 2018)
Background: Restless Leg Syndrome (RLS) is a common disorder in the elderly, especially older women, which causes sleep disorders and endangers the elderly with increase in the risk of falling, memory disturbances, and eventually, poor quality of life. Today, non-pharmacological approaches, including reflexology massage, are considered along with pharmaceutical methods for improving sleep quality. This study aims to examine the effect of foot reflexology massage on the sleep quality of the elderly women with RLS. Methods: The was a non-randomized clinical trial with a control group (quasi-experimental design) conducted on 67 elderly women with RLS resident in nursing homes located in Fars Province of Iran. Samples were selected using convenience sampling method. By tossing a coin, some elderlies were selected and allocated in the control and test groups. Foot reflexology intervention comprised eight 20-minute sessions (10 min for each foot) for 4 weeks. Pittsburgh Sleep Quality Index (PSQI) and a demographic questionnaire were used for collecting data which were administered before and after the intervention. The collected data were analyzed in SPSS V. 16 using descriptive statistics and inferential statistics such as Independent t test, paired t test, Fisher exact test, and Chi-squared test at a significance level of P<0.05. Results: The Mean±SD ages of the participants in test and control group were 71.43±6.25 and 72.6±4.67 years, respectively and both groups were matched in terms of age (P=0.389). There was no significant difference in sleep quality of the control group before and after the intervention (P=0.013 or 0.13), while in the test group the difference was statistically significant (P<0.001). In addition, the difference in RLS pain scores before and after the intervention was significantly lower in the test group compared to the control group (P<0.001). Conclusion: Foot reflexology massage had a positive effect on the sleep quality of the elderly women with RLS. Caregivers and nurses of the elderly are recommended to learn and use this easy and almost cost-free intervention for their patients.